Marriage Dispensation Orders: Judicial Product or State Administrative Decision - Lely Mahartina Khoiru Ummah; Lilia Prasastiningtyas (Yayasan Kawanad, 2026)
The amendment to the minimum marriage age through Law Number 16 of 2019 has led to a marked rise in applications for marriage dispensation before the Religious Courts, prompting a conceptual question regarding the legal standing of such orders — whether they ought to be read purely as judicial products or as state administrative decisions. Through normative legal research employing statutory and conceptual approaches, this study analyzes the juridical character of marriage dispensation orders and examines whether they satisfy the criteria of a state administrative decision, namely concreteness, individuality, finality, and the production of legal consequences, within the framework of administrative law. The findings reveal that marriage dispensation orders carry a hybrid character: procedurally issued as judicial products by the Religious Courts, yet substantively displaying characteristics of administrative decisions given that they constitute concrete, individual, and final grants of permission. This ambiguity signals the relevance of applying the general principles of good governance (AUPB) — particularly the principles of prudence and the protection of the best interests of the child — in adjudicating dispensation cases, and leads this study to advance the conceptualization of marriage dispensation orders as a judicialized administrative act, drawing attention to the intersection between judicial authority and administrative decision-making in the Indonesian legal system.